Failure behavior and energy evolution characteristics of deep roadway sandstone under different microwave irradiation modes - Tang, Mao-ying; Gao, Ming-zhong; Li, Shu-wu; Yang, Ben-gao; Tang, Rui-feng; Li, Fei; Liu, Jun-jun (Journal of Central South University, 2023)
Efficient breaking of hard rock and prevention and control of rock burst disasters are two key concerns for construction in deep areas with high in-situ stresses and are two of the most important ways to ensure the safe and efficient construction of deep engineering. Therefore, this study considers microwave weakening and fracturing of hard rock, taking the duration of a single microwave irradiation treatment as a variable, and synchronously combines mechanical testing and acoustic emission monitoring methods to demonstrate the possibility of rock burst disaster prevention and the control with this treatment method. The result shows that under microwave irradiation, the proportion of crack damage stress decreased from 77% to 62%; the proportion of dissipated energy increased from 6% to 20%, and the energy-based brittleness index also decreased from 0.94 to 0.72; acoustic emission monitoring found that after microwave irradiation, the quiet stage of the rock was greatly reduced from 56.2% and 59.6% to 11.5% and 8.6% with the monitoring time. In this test, the threshold of the duration of 1 kW microwave irradiation is 2 min; beyond this threshold, the rock is irreversibly damaged. The research results can provide necessary theoretical support and technical guidance for efficient and safe rock breaking in deep areas with high in situ stresses.